USING THE SOLIDWORCS SOFTWARE PRODUCT FOR DETERMINING THE MASS, KINEMATIC AND DYNAMIC CHARACTERISTICS OF THE MOVEMENT OF OBJECTS OF A COMPLEX VOLUME GEOMETRICCONFIGURATIONS - HOROKHOVSKYI, VIKTOR; HORDIEIEV, ANATOLYI (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Solving scientific tasks, which consist in the implementation of information technologies for support and decision-making in the synthesis and analysis of complex technological systems, taking into account the spatial geometry of components, is an urgent task for various technical branches of the national economy. The work deals with the issue of engineering analysis of technical systems by means of computer modeling, in particular, the calculation of kinematic and dynamic characteristics of complex objects, namely vehicles moving along different trajectories, using the SOLIDWORKS engineering analysis system, which allows using numerical experiments to determine their characteristics, namely mass, coordinates of the center of gravity of critical speeds in order to increase the accuracy of calculations in the analysis of a road traffic accident (traffic accident). To solve the problem of determining the critical speeds when the vehicle moves on a turn with a rollover, a technique based on computer modeling in SOLIDWORKS is proposed. For this, a 3-D model of a complex moving object is being built, to which various cargo can be added from a location in the desired city. The obtained results in the form of graphs make it possible to analyze the influence of various parameters of a complex moving object when turning and overturning, namely the height of the center of gravity, the radius of rounding of the road, the magnitude of the road slope, the condition of the road surface. The analysis of the results of the calculations of the critical rollover speed at the turn, according to the recommended range, showed that for the real values ​​of the height of the center of gravity, obtained according to the proposed methodology, the critical speed is lower according to the upper limit of the range when the road is flat, and also lower when the road is inclined at an angle β. The obtained results can be applied when conducting expert forensic studies to improve the quality of conclusions.